The Initial Coin Offering (ICO) process: Regulation and risks - Oksana A. Karpenko; Tatiana K. Blokhina; Lali V. Chebukhanova (Journal of Risk and Financial Management, 2021)
ICOs are very attractive for investors and issuers. ICOs allow funding raising in exchange for cryptographically secure tokens, which are a means of paying for future projects or services. However, there is insignificant regulation of this process all over the world. Some countries have banned crypto assets; others have allowed the free use of tokens but do not give them official status. In this paper, the authors present an overview of the legal regulation of ICOs in different countries, dividing them into three groups: in the first group are the countries with developed legal norms and rules for conducting ICO, they have the subsequent circulation of tokens on their territory; in the second group are the countries that are most friendly to ICOs; the third group of countries has a wait-and-see attitude. The author connect the insufficient law regulation and risks of ICOs in different countries. The types of ICO risks are divided into three main categories: financial, technical, and analytical. The main ways to reduce these risks, depending on their types, are highlighted in this study. They are connected with the improvement of the legal regulation of the publication of a White Paper, the KYC procedure, and the involvement of escrow agents.
Keywords: 330; ICO; crypto asset; regulation of ICO; successful ICO; ICO risks; White Paper of ICO; ICO platforms; funding of ICO projects